2015
DOI: 10.1080/10168737.2015.1020324
|View full text |Cite
|
Sign up to set email alerts
|

The Euro Effect on Eurozone Exports

Abstract: In this article, we examine the impact of the real effective exchange rate for several countries in the Euro area over the period before and after the introduction of the euro. Based on ARDL modeling techniques, we estimate the long-run and short-run relationships between exports volumes and a number of key variables, namely Real Effective Exchange Rate, weighted GDP and Output Gap. This article is particularly oriented towards the study of long-term relationships between the exchange rate and global exports p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Murphy and Siedschlag (2011) estimated that monetary integration had positive, significant and increasing effect on export. Bouchoucha (2015) analysis showed that the real effective exchange rate has bigger impact on exports between euro area countries than on global exports. Recent research (Sousa et al, 2008;Maurel, 2009;Carole, 2009;Katsikeas et al, 2010;Moghaddam et al, 2011;Stioan et al, 2011) reveals that export driving determinants can be divided into two groups: internal and external.…”
Section: Literature Review On Economic and Monetary Integration And Dmentioning
confidence: 99%
“…Murphy and Siedschlag (2011) estimated that monetary integration had positive, significant and increasing effect on export. Bouchoucha (2015) analysis showed that the real effective exchange rate has bigger impact on exports between euro area countries than on global exports. Recent research (Sousa et al, 2008;Maurel, 2009;Carole, 2009;Katsikeas et al, 2010;Moghaddam et al, 2011;Stioan et al, 2011) reveals that export driving determinants can be divided into two groups: internal and external.…”
Section: Literature Review On Economic and Monetary Integration And Dmentioning
confidence: 99%
“…This paper extends the works of the impacts of real depreciation on imports and exports by Stučka, (2003), Breuer and Klose (2015) and Bouchoucha (2015) and examines the impact of real depreciation on aggregate demand and aggregate output. The contribution of the paper is that the theoretical model extends the IS-MP-AS model (Romer, 2000(Romer, , 2006 and consists of additional new variables such as the real exchange rate, world real income, the world real interest rate, and the real oil price so that international trade, open economy and supply shocks are considered.…”
Section: Introductionmentioning
confidence: 99%
“…In assessing the impact of the Euro exchange rate on exports, Bouchoucha (2015) reveals that the effect of the real effective exchange rate of the euro on intra-euro area exports is greater than that on global exports and that the effect of the real effective exchange rate of the euro on exports before and after the EMU also differs. He also indicates that Italy and Spain have more structural problems than price competitiveness due to the insignificance of the real effective exchange rate of the euro.…”
Section: Literature Surveymentioning
confidence: 99%
“…France saw its cost competitiveness vis-à-vis Germany (its biggest export competitor) deteriorate during the 2000s (Bouchoucha, 2015;Kierzenkowski, 2009). The introduction of the EMU in a set of countries with different wage-setting institutions led to a divergence in real unit labor costs and consequently current account balances (Carlin, 2013;De Grauwe, 2013;Johnston et al, 2014).…”
mentioning
confidence: 99%